Coordination Patterns and Energy Flow Analysis in Sit-to-Stand Transitions Among Individuals with Different Body Mass Indexes - Lei Li; Xuan Liu; Ye Liu (Life)
Background: This study investigates the differences in limb coordination patterns and energy transfer strategies during sit-to-stand (STS) transitions among young adults (18–30 years) with overweight (OW), normal weight (NW), and underweight (UW) conditions, providing a theoretical foundation for understanding the impact of BMI variations on movement control mechanisms and informing health intervention strategies. Methods: Forty participants were classified into OW, NW, and UW groups. Motion data were collected via an infrared motion capture system and force plate. Biomechanical indices were computed using Visual 3D and MATLAB2020a. Coordination patterns were assessed using vector coding, and the segmental net power was analyzed to evaluate energy flow during STS. Statistical analyses were performed using one-way ANOVA (α = 0.05). Results: Compared to the NW and UW groups, the OW group exhibited significant differences in movement coordination patterns and energy flow. In terms of coordination patterns, the OW group adopted more hip-knee distal coordination patterns in the FMP phase and more knee-ankle proximal coordination patterns. In the MTP phase, the OW group exhibited a lower frequency of hip-ankle anti-phase coordination patterns compared to the UW group. In the EP phase, the OW group showed a lower frequency of trunk-pelvis proximal coordination patterns than the UW group (p < 0.05). Regarding energy flow, in the FMP phase, the OW group exhibited higher joint power (JP) and segment power (SP) in the trunk compared to the UW group. In the pelvic segment, both JP and SP were higher in the OW group than in the NW and UW groups. In the thigh segment, muscle power (MP) was higher in the OW group than in the NW and UW groups, and SP was higher than in the NW group (p < 0.05). Conclusion: Changes in BMI affect movement coordination and energy transfer strategies during STS. OW individuals compensate for insufficient hip drive by relying on trunk and pelvic power, which may increase the knee and trunk load over time. In contrast, UW individuals exhibit greater lower-limb flexibility and rely on trunk-pelvis coordination to compensate for stability deficits. Future research should develop targeted exercise interventions to optimize movement patterns and reduce injury risk across BMI groups.